THE MEDIATION INFLUENCE OF VALUE RELEVANCE OF ACCOUNTING INFORMATION, INVESTMENT DECISION AND DIVIDEND POLICY ON THE RELATIONSHIP BETWEEN PROFITABILITY AND THE COMPANY’S VALUE - Harnovinsah, Harnovinsah; Alamsyah, Sustari (Jurnal Akuntansi, 2017)
This study aimed to analyze the influence of profitability on the company's value, and determine whether this influence intervenes the value relevance of accounting information, investment opportunities and dividend policy, assuming that investors act rationally so that the fundamental aspects of the financial statements become major factor in the shares investment decision. The contribution of this research is to provide input to the management about the importance of maintaining and improving performance in order to give satisfaction to investors and provide expectations for the return on investment which can ultimately increase the company’s value. This study design is causality with the unit of analysis is the samples taken by purposive sampling technique on a population of listed companies on the IDX Kompas 100 index from 2011 - 2014. The analysis technique used is Path Analysis. The results from this study are: 1. Profitability has significant and positive influence on the company’s value; 2. Profitability has no significant and positive influence on the value relevance of accounting information; 3. Profitability has negative and significant influence on investment opportunities; 4. Profitability has significant and positive influence on the dividend policy; 5. The value relevance of accounting information has significant and negative influence on the company’s value; 6. The investment opportunities have no significant and positive influence on company’s value; 7. Dividend policy has no significant and positive influence on company’s value; 8. The value relevance of accounting information, investment opportunities and dividend policy have not been able to mediate the influence of profitability on company’s value.